ANALISIS PROFIT SHARING DALAM AKUNTANSI SYARIAH PADA PT. BANK SYARIAH MANDIRI KANTOR CABANG PEMBANTU GOWA DI KABUPATEN GOWA - riska, riska; Mansyur, fakhruddin (Jurnal Ar-Ribh, 2019)
The objective of this research is to know the accounting treatment of earnings for syariah bank and to evaluate the suitability between accounting treatment of revenue sharing in syariah bank with the provisions according to PSAK no. 105 about revenue sharing. The research object is PT Bank Syariah Mandiri KCP Gowa. The results showed that a). the accounting treatment for financing of sharia banking with a mudharabah contract is related to profit, when the customer gains profit from the business it manages, PT Bank Syariah Mandiri KCP Gowa will recognize revenue-sharing upon the occurrence of profit sharing rights in accordance with the ratio (profit sharing) mutually agreed upon at the start of the agreement. b). The accounting treatment of income in PT Bank Syariah Mandiri mudharabah has been able to comply with the provisions of PSAK No.105 regarding profit sharing.